Plasma growth arrest-specific 6 levels in term and preterm newborns - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2018)
Objective: Growth Arrest-Specific 6 (GAS6) is a vitamin K-dependent protein. Despite a similar structure to Protein S, it has no anticoagulant activity. An association between GAS6 and some diseases for adults has been reported. In the absence of prospective clinical studies of GAS6 in neonates, so far, the objective of this study is to obtain, for the first time, plasma GAS6 levels before and after vitamin K1 prophylaxis in full-term and pre-term newborns.Methods: 80 newborns (40 term and 40 preterm) were recruited for this study. Cord blood samples and peripheral blood samples 48h after vitamin K1 injection were collected into EDTA-tubes. GAS6 levels were measured in platelet-poor plasma by ELISA.Results: Cord blood plasma GAS6 levels in preterm and term newborns were 9.075.30ng/mL and 9.75 +/- 4.34ng/mL, respectively. In response to vitamin K1 injection, GAS6 levels increased in preterm newborns (10.50 +/- 5.28ng/mL) (p<.05), but not in term newborns (9.12 +/- 3.42ng/mL, p>.05).Conclusion: This pilot study provided, to the best of our knowledge, the first report that GAS6 levels increased significantly after vitamin K1 prophylaxis in preterm newborns but not in term infants. This study may serve as a first step toward more extensive studies in neonates.
Keywords: GAS6; vitamin K; newborn; term; preterm; fetal growth retardation; TYROSINE KINASE; PROTEIN; GAS6; PREGNANCY; PROTHROMBIN; ASSOCIATION; SYSTEM; FAMILY; CELLS; GENE